CHARACTERIZATION AND IDENTIFICATION OF STRAIN KM221, A NOVEL MCPA HERBICIDE-DEGRADING BACTERIUM ISOLATED FROM CORAL SURFACE, MENJANGAN KECIL ISLAND, KARIMUNJAWA - Agus Sabdono; Ocky Karna Radjasa; Joedoro Soedarsono (JOURNAL OF COASTAL DEVELOPMENT, 2003)
In this study, bacterial strain KM221 was isolated from coral   tissue in Menjangan Kecil Island, Karimunjawa, Indonesia. This strain is  facultative anaerobic  with MCPA (2-methyl-4-chlorophenoxy acetic acid) serving as the only known energy sources.  Microscopy  of isolate revealed that strain KM221 is gram-positive, catalase-positive,  rod, spore-forming bacterium, motile,  opaque, hair-like outgrowth and unpigmented colonies. The bacterium could not be identified on the basis of its carbon-source-utilization pattern, but a partial sequencing of the 16S rDNA analysis suggest that this strain is closely related to Bacillus iodinum.The ability to degrade MCPA herbicide was examined qualitatively in EMBA indicator medium.  This bacterium grew exponentially with MCPA as  the sole source of energy and carbon. The maximum growth rate (m max)  and the  saturated concentration on MCPA (Cs) were determined to be  0.8024 h-1 and  5.10 mg/l MCPA, respectively.